TREND OF MALARIA TRANSMISSION 2018-2022 AND ELIMINATION AGENDA IN MAPPI DISTRICT - Doni Lasut; Maria Holly Herawati (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
The WHO Global Malaria Programme (GMP) oversees and directs the global initiatives of the World Health Organization (WHO) aimed at controlling and eradicating malaria.. Its work is guided by the "Global Technical Strategy for Malaria 2016–2030. Mappi district a high endemic area in South Papua Province was still combat to eliminate malaria transmission. However, the spread and transmission of malaria differ across different regions. The study sought to analyze the distribution and extent of malaria over a five-year period within the Mappi District and the operational areas of its Public Health Centers (PHCs). A Retrospective study was Weekly surveillance data was gathered over a five-year period from 2018 to 2022. The data was collected from health facilities and private clinics, archived at zonal Public Health Centers (PHCs), and conducted in the intentionally selected Mappi District in South Papua Province. The data was gathered, entered, cleaned, analyzed, and interpreted using Microsoft Excel 2019. Various tables, figures, and maps were employed to display the results. Age 15-64 (41%) was the highest proportion of cases, with male proportion (54,46%) higher than female(45,54%), Paracites were dominated by Plasmodium falciparum (65,84%), Malaria test are dominated by microscope (56,25%) than RDT (43,75%), Average Annual Paracites Index (API) was 46,9 per 1000. The trend shows us elimination as GMP and National Strategy in Indonesia in 2030 need more effort to decrease the malaria transmission in Mappi District, The most prevalent malaria parasite species were Plasmodium falciparum and Plasmodium vivax. The magnitude of API at Kumaban, Sammad, and Sekko area. Attention is required to expand vector control measures during periods of high malaria transmission.